(untitled) (Proceedings of the International Conference on Future of Education, 2020)
For a long period of time, Faculty of Education, Chiang Mai University has offered the study program on Thai language and culture program for foreign students and foreigners interested in studying Thai language and culture. Every year, there are exchange Japanese students who are interested to study Thai language and culture there. The purpose of this research was to study the needs of Japanese students who study Thai language and culture at Chiang Mai University. The sample used was specifically selected from Japanese students who study Thai language and culture. There are 46 students 23 whom studying at Kokushilkan University and 23 studying at Kanda University of International Studies. The tools used for data collection are questionnaires. The quantitative data were analyzed in terms of percentage, mean and standard deviation. It was found that the needs for learning Thai language and culture in all 7 parts were with 4.26 mean at very high level. The needs along descending order of the least 7 ones are the needs for 1) contents learning which was with 4.57 mean and at highest level, 2) reasoning in Thai language which was with 4.39 mean and at high level, 3) teaching and learning management which was with 4.31 mean and at high level, 4) learning support for Thai language and culture of students which was with 4.29 mean and at high level, 5) learning measurement and evaluation which was with 4.18 mean and at high level, 6) teaching and learning materials and equipment which was with 4.13 mean and at high level, and, 7) purpose of learning Thai language and culture which was with 3.98 mean and at high level.